PERAN BABINSA DAN MAHASISWA TERHADAP PERUBAHAN PERILAKU PETANI DALAM PROGRAM UPAYA KHUSUS PADI JAGUNG DAN KEDELAI DI KECAMATAN PARON KABUPATEN NGAWI - Bekti Nur Utami; Deha Purwoko (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
The purpose of this research is determine : (1) Babinsa role, (2) college student role and (3) Changes of farmers behavior in the Program Efforts Special Rice Corn and Soybean. The data collection is done by observation, interviews, focus group discussions, documentation. Sample of 60 people with simple random sampling. The results showed: (1) Babinsa role : (A) Mobilizing and motivating farmers; (B) Implement support in certain circumstances; (C) Implement supervision of administrative filing and distribution of aid to beneficiaries; and (D) Conducting oversight of the activities of identification, data collection and reporting of technical implementation of the activities.; (2) Student college role: (A) Escort and assistance for the implementation of the GP-PTT, POL, RJIT, PAT and demfarm, (B) Introduction of technology, (C) Develop a model empowerment of farmers, (D) Develop networks and businesses partnerships, and (E) Identify data collection and reporting of the activities. Extension to solve the problems encountered in the field, resulting in changes in the farmer behavior include aspects: (a) knowledge, (b) attitudes, and (c) skills. Babinsa and college student role is very favorable to the smooth UPSUS Pajale Program and directly advantage farmers.